2020
DOI: 10.3390/jcm9040975
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric Functional Connectivity in the Primary Motor Cortex Assessed by Resting-State Functional Magnetic Resonance Imaging Aids Long-Term Recovery Prediction among Subacute Stroke Patients with Severe Hand Weakness

Abstract: This study aimed to evaluate the usefulness of interhemispheric functional connectivity (FC) as a predictor of motor recovery in severe hand impairment and to determine the cutoff FC level as a clinically useful parameter. Patients with stroke (n = 22; age, 59.9 ± 13.7 years) who presented with unilateral severe upper-limb paresis and were confirmed to elicit no motor-evoked potential responses were selected. FC was measured using resting-state functional magnetic resonance imaging (rsfMRI) scans at 1 month fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…The obstruction of the great vessels could directly result in ischemic necrosis of the brain functional units within the cerebral cortex (4). Previous studies of stroke suggested that the functional connectivity (FC) in the supplementary motor area, the inferior temporal gyrus, and the middle occipital gyrus differs from that of normal participants (5). Additionally, significant abnormalities were found in the cognitive networks of stroke patients, such as the default network (DMN), and the somatic motor network (SMN) (6).…”
Section: Introductionmentioning
confidence: 99%
“…The obstruction of the great vessels could directly result in ischemic necrosis of the brain functional units within the cerebral cortex (4). Previous studies of stroke suggested that the functional connectivity (FC) in the supplementary motor area, the inferior temporal gyrus, and the middle occipital gyrus differs from that of normal participants (5). Additionally, significant abnormalities were found in the cognitive networks of stroke patients, such as the default network (DMN), and the somatic motor network (SMN) (6).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the ipsilesional primary motor cortex was identified in several significant connections across time points, which is consistent with published studies that found it to be a main target for stroke neurorehabilitation ( Buetefisch, 2015 ; Tsuchimoto et al, 2019 ). Moreover, the supplementary motor areas have been shown to play a functional role in both motor imagery and motor planning ( Min et al, 2020 ), therefore, increases in rsFC strength exhibited between the ipsilesional and contralesional supplementary motor areas after BCI training may be a form of adaptive motor network reorganization. In addition, connectivity between the ipsilesional and contralesional primary motor cortex strengthened after intervention, which supports previous findings of increases in M1-M1 connectivity after rehabilitation that correlated with improved recovery outcomes ( Fan et al, 2015 ; Min et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proved that FC values are positively correlated with the patients' motor function recovery [20][21][22]. The different FC values in the interhemispheric motor cortex (M1) after stroke can re ect long-term recovery of motor function, which makes FC a predictor of motor function recovery [23]. In this study, we will determine the bilateral cerebral FC values to explore the mechanisms underlying the cerebral remodeling after stroke.…”
Section: Neuroimaging Outcomesmentioning
confidence: 99%